HUBUNGAN ANTARA MOTIVASI KERJA DAN KEDISIPLIN DENGAN KINERJA GURU DI SD - Didik Fredianto (Manajer Pendididikan, 2016)
This study aims to determine the relationship motivation and discipline against teacher performance in public elementary school Batik Nau North Bengkulu. The method used descriptivequantitative. Data was collected using a questionnaire and analyzed using correlation and regression techniques. The results showed that there is a positive relationship between themotivation of teachers working with teachers. There is a positive relationship between the discipline of teachers working with teachers. There is a positive relationship between motivationand discipline of teachers working together on teacher performance. motivation and discipline of work have a positive relationship to the performance of teachers.Keywords: motivation, discipline, teacher performance